Vitamin D during pregnancy and neurodevelopment of the child: systematic review. - Villalobos, Marcela; Tous, Monica; Canals, Josefa; Arija, Victoria (Anales de Psicología / Annals of Psychology, 2019)
Background: A deficiency of vitamin D during pregnancy has a negative impact on the health of the mother and the child. Objective: To evaluate the effect of vitamin D status during pregnancy on the neurodevelopment of children. Selection of studies: We explored studies that linked the maternal status of vitamin D with neurodevelopment in the infant. The selected studies were identified through a systematic review of the scientific literature published in PubMed/MEDLINE, Scopus and Cochrane until January 2018. The quality of the included studies was carried out through the Newcastle-Ottawa scale. Results: 164 studies were identified and reviewed for selection. At the end of this review, 11 studies were included, all of high methodological quality. This systematic review shows that prenatal vitamin D levels <50 nmol/L are associated with worse mental, motor and language development of their children compared with pregnant women with good vitamin D status. Conclusion: There is still little scientific evidence to corroborate the relationship between prenatal vitamin D deficiency and its impact on the neurodevelopment of children, although current data suggest a detrimental effect on the child’s mental, motor and language development.